2011
DOI: 10.2169/internalmedicine.50.5891
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese Case with Nasu-Hakola Disease of DAP12 Gene Mutation Exhibiting Precuneus Hypoperfusion

Abstract: A 38-year-old Japanese man with Nasu-Hakola disease (NHD) had repeated pathological fractures and frontal lobe symptoms which developed when he was 18 and 26 years old, respectively. Neuropsychological testing showed memory impairment, and in particular, visuo-spatial memory at the age of 35. Furthermore, single-photon emission computed tomography revealed precuneus hypoperfusion. The patient later suffered prolonged convulsive seizures, which left him in a persistent vegetative state. Genetic testing confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The present study includes five NHD patients, composed of a 42-year-old man (NHD1), a 48-year-old woman (NHD2), a 44-year-old man (NHD3), a 32-year-old woman (NHD4), and a 38-year-old man (NHD5), four neuropsychiatric disease controls affected with myotonic dystrophy (MD), composed of a 68-year-old man (MD1), a 61-year-old man (MD2), a 60-year-old man (MD3), and a 53-year-old woman (MD4), four demyelinating disease controls affected with chronic progressive multiple sclerosis (MS), composed of a 29-year-old woman (MS1), a 40-year-old woman (MS2), a 43-year-old woman (MS3), and a 33-year-old man (MS4), and four subjects who died of non-neurological causes (NC), composed of a 63-year-old man who died of prostate cancer and acute myocardial infarction (NC1), a 67-year-old man who died of dissecting aortic aneurysm (NC2), a 57-year-old man who died of alcoholic liver cirrhosis (NC3), and a 61-year-old man who died of rheumatoid arthritis with interstitial pneumonia (NC4). The homozygous mutation of a single base deletion of 141G (141delG) in exon 3 of DAP12 was identified in NHD1, NHD2, and NHD5 [19,26], while the genetic analysis was not performed in NHD3 [27] or NHD4 [28]. …”
Section: Methodsmentioning
confidence: 99%
“…The present study includes five NHD patients, composed of a 42-year-old man (NHD1), a 48-year-old woman (NHD2), a 44-year-old man (NHD3), a 32-year-old woman (NHD4), and a 38-year-old man (NHD5), four neuropsychiatric disease controls affected with myotonic dystrophy (MD), composed of a 68-year-old man (MD1), a 61-year-old man (MD2), a 60-year-old man (MD3), and a 53-year-old woman (MD4), four demyelinating disease controls affected with chronic progressive multiple sclerosis (MS), composed of a 29-year-old woman (MS1), a 40-year-old woman (MS2), a 43-year-old woman (MS3), and a 33-year-old man (MS4), and four subjects who died of non-neurological causes (NC), composed of a 63-year-old man who died of prostate cancer and acute myocardial infarction (NC1), a 67-year-old man who died of dissecting aortic aneurysm (NC2), a 57-year-old man who died of alcoholic liver cirrhosis (NC3), and a 61-year-old man who died of rheumatoid arthritis with interstitial pneumonia (NC4). The homozygous mutation of a single base deletion of 141G (141delG) in exon 3 of DAP12 was identified in NHD1, NHD2, and NHD5 [19,26], while the genetic analysis was not performed in NHD3 [27] or NHD4 [28]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition to affecting oligodendrocyte survival and recovery following demyelination, TREM2 variants in PLOSL have also elucidated other roles of TREM2 in NDDs. PLOSL patients often experience seizures [ 22 , 310 ], resulting in excitotoxicity. One patient with a predicted loss-of-function TREM2 PLOSL mutation had a reduction in many synaptic components, including nine GABA receptor subunits, which could play a role in mediating this enhanced excitability [ 28 ].…”
Section: Trem2 and Ndd Pathologymentioning
confidence: 99%
“…Occasionally, also cerebellar atrophy has been found [25]. Not only white matter, but also grey matter changes have been reported in PLOSL [25,30,31]. Aoki et al [31] reported on 3 autopsy cases with PLOSL.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the long duration of the disease and repeated epileptic convulsions have contributed to the severity of the grey matter lesions, particularly in the hippocampus. Nakamagoe et al [30] reported on a PLOSL patient in whom behavioural abnormalities were detected at the age of 26 years. At the age of 34 years, MRI of the brain revealed diffuse high-intensity areas in the white matter as well as hippocampal atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation